Arterial hypertension prevalence in type 2 diabetes patients (Analysis of Bashkortostan Republic State Diabetes Registry data) - E. Kh. Akhmetzyanova; D. U. Allaberdina (Российский кардиологический журнал)
Arterial hypertension (AH) prevalence in Type 2 diabetes mellitus (DM) was studied in adult population (aged above 18 years) of Bashkortostan Republic (BR), according to WHO/ISH criteria (1999). The data were taken from the BR State DM Registry (SDMR). AH prevalence (blood pressure at least 140/90 mm Hg) was 70, 1 % (73, 9 % in females, 69, 3 % in males). In women, advanced AH stages were registered more often than in males. There was a weak correlation of female gender and AH in type 2 DM (r=0, 09).